Children's Vulnerability to Interparental Conflict: The Protective Role of Sibling Relationship Quality. Issue 6 (19th June 2018) - Davies, Patrick T.; Parry, Lucia Q.; Bascoe, Sonnette M.; Martin, Meredith J.; Cummings, E. Mark
Abstract : This study tested whether the strength of the mediational pathway involving interparental conflict, adolescent emotional insecurity, and their psychological problems depended on the quality of their sibling relationships. Using a multimethod approach, 236 adolescents ( M age = 12.6 years) and their parents participated in three annual measurement occasions. Tests of moderated mediation revealed that indirect paths among interparental conflict, insecurity, and psychological problems were significant for teens with low, but not high, quality bonds with siblings. High‐quality (i.e., strong) sibling relationships conferred protection by neutralizing interparental conflict as a precursor of increases in adolescent insecurity. Results did not vary as a function of the valence of sibling relationship properties, adolescent sex, or gender and age compositions of the dyad.